Trudności diagnostyczne nieleczonej torbieli zastoinowej wargi górnej = Diagnostic difficulties of not treated congestive cyst of the upper lip - Ratajek-Gruda, Monika; Grzejszczak, Marta; Janas-Naze, Anna (Journal of Education, Health and Sport, 2016)
Ratajek-Gruda Monika, Grzejszczak Marta, Janas-Naze Anna. Trudności diagnostyczne nieleczonej torbieli zastoinowej wargi górnej = Diagnostic difficulties of not treated congestive cyst of the upper lip. Journal of Education, Health and Sport. 2016;6(12):604-613. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.217618 http://ojs.ukw.edu.pl/index.php/johs/article/view/4105 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 22.12.2016. Trudności diagnostyczne nieleczonej torbieli zastoinowej wargi górnej Diagnostic difficulties of not treated congestive cyst of the upper lip Monika Ratajek-Gruda, Marta Grzejszczak, Anna Janas-Naze Zakład Chirurgii Stomatologicznej Uniwersytecki Szpital Kliniczny nr 6 UM w Łodzi Kierownik: Prof. nadzw. dr hab. n. med. Anna Janas-Naze Zakład Chirurgii Stomatologicznej UM ul. Pomorska 251 92-213 Łódź dr n. med. Monika Ratajek-Gruda, lek. dent. Marta Grzejszczak, dr hab. n. med. prof. nadzw Anna Janas-Naze Praca finansowana przez UM w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001 Streszczenie: W pracy przedstawiono przypadek pacjenta, u którego pierwotne rozpoznanie dotyczyło ciała obcego w wardze górnej. Wynik badania histopatologicznego wykazał obecność torbieli zastoinowej małego gruczołu ślinowego z ropnym stanem zapalnym. Słowa kluczowe: torbiel zastoinowa, ciało obce Summary: The article describes case of patient with foreign body in upper lip as a first diagnosis. Histopathological analysis revealed presence of mucocele with purulent inflammation. Key words: mucocele, foreign body